The Indonesian Economy amidst the Global Crisis : Good Policy and Good Luck - Basri, Muhammad Chatib; Rahardja, Sjamsu (2012)
The global economic crisis has caused economic collapse in many countries. Indonesia is obviously affected by this crisis, its export growth declined significantly. Nevertheless, the impact of the crisis on the Indonesian economy is relatively limited compared to other countries in the region, including Singapore, Malaysia, and Thailand. This situation leads into a question of why the impact of the global crisis on the Indonesian economy is relatively limited so far. Is it because of the structure of Indonesia's trade or the effectiveness of Indonesia's fiscal policy and monetary response? This paper argues that there are at least two reasons why Indonesia's performance was relatively good. Firstly, it was due to the appropriate policy responses both from Bank Indonesia and the Indonesian government. Secondly, Indonesia's relatively small export share to GDP saved the country from the global financial crisis. This was more a case of good luck than deliberately planned economic policy strategy. Nevertheless, this paper indicates that exports are a source of Indonesia's economic growth. Exports have a large effect in supporting economic growth, albeit less stable compared to domestic demand. Because of this, a strategy safeguarding a balance between domestic economy and global orientation, such as becoming a part of a production network and promoting export-oriented growth, must be a part of the development strategy of the national economy.